Best Proximity Points of Multivalued Hardy-Roger's Type (Cyclic) Contractive Mappings of b-Metric Spaces. (24th January 2022) - Ali, Basit; Khan, Arshad Ali; Hussain, Azhar
Abstract : In this article, we introduce a new type of generalized multivalued Hardy and Roger's type proximal contractive and proximal cyclic contractive mappings of b -metric spaces and develop some results for the existence of best proximity point(s). Moreover, we obtain some results for the existence and uniqueness of best proximity points for single-valued mappings. Examples are given to explain the main results.